SIRT3 activation promotes enteric neurons survival and differentiation - Arun Balasubramaniam; Ge Li; Anita Ramanathan; Simon Musyoka Mwangi; C. Michael Hart; Jack L. Arbiser; Shanthi Srinivasan (Scientific Reports, 2022)
Abstract Enteric neuron degeneration has been observed during aging, and in individuals with metabolic dysfunction including obesity and diabetes. Honokiol, a naturally occurring compound, is an activator of Sirtuin-3 (SIRT3) that has antioxidant activity. Its role in modulating enteric neuron-specific neurodegeneration is unknown. We studied the effects of honokiol and its fluorinated analog, hexafluoro-honokiol, on enteric neuronal differentiation and survival. We used a previously established model of mouse primary enteric neuronal cells and an enteric neuronal cell line treated with palmitate (PA) and lipopolysaccharide (LPS) to induce mitochondrial dysfunction and enteric neuronal cell death. The effect of honokiol and hexafluoro-honokiol was assessed on neuronal phenotype, fiber density, differentiation, and pyroptosis. Honokiol and hexafluoro-honokiol significantly increased neuronal networks and fiber density in enteric neurons and increased levels of neuronal nitric oxide synthase and Choline acetyltransferase mRNA. Hexafluoro-honokiol and honokiol also significantly increased SIRT3 mRNA levels and suppressed palmitate and LPS-induced neuronal pyroptosis. SIRT3 knock-down prevented the hexafluoro-honokiol mediated suppression of mitochondrial superoxide release. Our data supports a neuroprotective effect of honokiol and its derivative and these could be used as prophylactic or therapeutic agents for treating enteric neurodegeneration and associated motility disorders.